Audiometric outcomes following radiosurgery for vestibular schwannoma treatment: the IPOC-FG experience - Medeiros, Nuno (2021)
Introduction: Vestibular Schwannoma (VS) corresponds to 8% of all intracranial lesions. Although many patients present themselves with important hearing loss, its worsening is still a major concern. Material and Methods: Retrospective study involving patients suffering from VS who received RadioSurgery from June 2013 until December 2020. Pure tone and speech audiometry were conducted before and after GKRS. Results: 43 patients (55.8% females; mean of age 59.7 y.o) were analyzed.. Mean tumor size of 17.6mm pre-radiosurgery and 16.4mm post-radiosurgery. Ipsilateral PTA mean was 76.1+/- 25.4 dB HL pre-procedure and 84.3 +/- 28.1 post-procedure. Only 11 patients presented serviceable hearing pre-procedure, with 89.8% maintaining it at max follow-up. No significant changes occurred in the contralateral ear PTA mean. Hearing level preservation was not dependent on pre-treatment hearing class (p=0.59), tumor size pre-procedure (p=0.8) sex (p=0.35) or patient age (p=0.42) in our study. Conclusions: Hearing deterioration occurred in one-third of the patients in ipsilateral but not in contralateral hearing. Important factors affecting hearing preservation described in other studies were not statistically significant in our sample